Experimental and numerical investigation of the creep behaviour of Ni‐based superalloy GH4169 under varying loading. Issue 5 (29th December 2017) - Wei, D.S.; Wang, J.L.; Wang, Y.R.; Zhong, B.
Abstract: The high‐temperature creep experiment of Ni‐based superalloy GH4169 under the constant loading and varying loading conditions was conducted by using the round bar specimens. The creep time‐strain curves under different loading conditions were obtained to study the high‐temperature creep behaviour of GH4169 superalloy. At the same time, the longitudinal and lateral sections near the fracture of creep specimens were observed by the optical microscope, and the specimens with smaller grain corresponded to the larger creep strain rate. In view of the dispersion of the creep curves, the corresponding data processing method was put forward, and on this basis, a model that can describe the 3 stages of creep with certain physical meaning was established. The simulation results are in good agreement with the experimental results, especially the creep deformation under the varying loading condition. The predicted results of the relative time hardening model are closer to the experiment compared with time hardening and strain hardening model. The creep model is realized by the user's material subroutine code in a commercial FEM software package, which can be used as the basis of creep analysis for engineering structures.